Exploring perceptions towards health and child nutrition: A qualitative study among tribal mothers in Southern Karnataka - Sowmya Pujari; Ranjitha S. Shetty; Suneel C. Mundkur; Elsa Sanatombi Devi; Amol Dongre; B. Unnikrishnan; Sreedharan Nair (PLoS ONE, 2026)
Background Malnutrition accounts for nearly one-third of child deaths globally and continues to be a major concern in India. Despite economic progress, undernutrition remains prevalent, with one-third of children underweight and over two-thirds anemic. Within India, marginalized groups such as the Koraga tribe face greater risks due to poverty, limited healthcare access and cultural barriers that compound child health challenges. Understanding maternal perceptions is crucial to effectively address these challenges. Methods In-depth interviews were conducted with Koraga tribal mothers of children aged 5–10 years. Participants were selected using criterion-based purposive sampling to ensure representation across different age groups and household contexts. Interviews were audio-recorded in local languages (Tulu and Kannada), transcribed verbatim, translated into English and analysed inductively using thematic analysis with NVivo software (version 14). Results Twenty Koraga tribal mothers were interviewed between October 2023- March 2024. Thematic analysis revealed five major themes: evolving perceptions of health and wellbeing; nutrition beliefs and practices; hygiene and health promotion; traditional healing with modern care and barriers and community solutions. These findings highlighted key challenges such as limited healthcare access, poverty and educational constraints, while also capturing community-driven strategies including reliance on health workers and government food-schemes. Conclusion Maternal perceptions, shaped by cultural norms and socioeconomic constraints, play a critical role in influencing health and child nutrition in the Koraga community. The findings highlight the need for policy measures that integrate culturally informed nutrition education with strengthened frontline health services, alongside community-based programs involving women’s self-help groups to improve health outcomes in marginalised tribal populations.